A survey of Scottish public service organisations - Kakabadse, Andrew P.; Myers, Andrew; Kakabadse, Nada K. (Cranfield University School of Management, 2007)
Around 280 Scottish public service organisations were contacted to take part in the survey into Chairman. Members from public services bodies such as the National Health Service, Higher Education establishments, and Voluntary Sector organisations were encouraged to ask other members of their Board to complete a short questionnaire.